REWRITING POWER: THE METAPOLITICS OF GENDER, IDENTITY, AND GLOBAL LEGITIMACY IN THE AGE OF FRAGMENTED GOVERNANCE - Khamraeva Asal Akmal qizi (Modern American Journals, 2025)
This article investigates the complex interplay between gender politics, identity, and global legitimacy in the contemporary era marked by fragmented governance. It explores how anti-gender mobilizations and backlash against progressive gender norms have become pivotal in reshaping political and social orders internationally. The study analyzes transnational conservative networks, rising illiberal populism, demographic anxieties, and global geopolitical realignments that challenge gender equality, feminism, and LGBTQ+ rights, undermining democratic norms and renewing cultural-political contestations over identity. Through review of recent legislative trends, activist repression, and coalition-building at multilateral institutions, the paper demonstrates how metapolitical struggles over gender both reflect and drive processes of democratic erosion and redefined power configurations.
Keywords: nservative networks, rising illiberal populism, demographic anxieties, and global geopolitical realignments